2012
DOI: 10.1111/j.1601-183x.2011.00759.x
|View full text |Cite
|
Sign up to set email alerts
|

Akt1 deficiency modulates reward learning and reward prediction error in mice

Abstract: In contemporary reinforcement learning models, reward prediction error (RPE), the difference between the expected and actual reward, is thought to guide action value learning through the firing activity of dopaminergic neurons. Given the importance of dopamine in reward learning and the involvement of Akt1 in dopaminedependent behaviors, the aim of this study was to investigate whether Akt1 deficiency modulates reward learning and the magnitude of RPE using Akt1 mutant mice as a model. In comparison to wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…RL models have been increasingly applied to study reward-based learning in humans, non-human primates, and mice (Juckel et al, 2006; Rutledge et al, 2009; Chen et al, 2012). During reinforcement learning, the firing of dopaminergic neurons has been found to correlate with the characteristics of prediction errors postulated in the RL models (Schultz et al, 1997; Montague et al, 2004; Glimcher, 2011), supporting the dopamine reward prediction error hypothesis (Glimcher, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RL models have been increasingly applied to study reward-based learning in humans, non-human primates, and mice (Juckel et al, 2006; Rutledge et al, 2009; Chen et al, 2012). During reinforcement learning, the firing of dopaminergic neurons has been found to correlate with the characteristics of prediction errors postulated in the RL models (Schultz et al, 1997; Montague et al, 2004; Glimcher, 2011), supporting the dopamine reward prediction error hypothesis (Glimcher, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Motivated by an earlier work by Frank et al (2004) of the role of dopamine on RPE in Parkinson's patients, Rutledge et al (2009) found that patients with Parkinson's disease, which is characterized by a deficit in dopamine neurons in the midbrain, increased their value-updating speed in a “dynamic foraging task” after L-DOPA (which is a direct precursor to dopamine) manipulation. Chen et al (2012) reported that Akt1 (which is one of the schizophrenia candidate genes and a downstream kinase for dopamine D2 receptors) mutant mice exhibit, on average, higher learning rates and lower degrees of exploitation than wild-type control mice in a “dynamic foraging T-maze.” Both studies indicate that the subjects give RPE signals greater weight and change their beliefs more frequently when their dopamine activity is increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the second cohort of male and female mice, total distances traveled (cm) were also recorded for a 60-min baseline period following the administration of saline and for two 60-min periods following methamphetamine injection. The doses of MK-801 and methamphetamine were chosen to avoid stereotypic behaviors in the open field as described previously (Wu et al, 2005; Van Den Buuse et al, 2009; Chen et al, 2012, 2014). The third cohort of male and female mice received an injection of PTZ to induce a seizure response, and their behaviors were videotaped and recorded in the chamber for 1 h. The dose of PTZ was chosen based on previous dose studies of C57BL/6 mice (Itoh and Watanabe, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Akt1 −/− mice display reduced body weight and altered metabolism (Wan et al 2012), neither of which are seen in schizophrenia, and it is possible that such alterations could play a role in the behavioral changes observed in these mice independent of the relationship between reduced Akt1 expression and schizophrenia symptomology. In contrast to fully homozygous Akt1 null mice, heterozygous mice express Akt1 at approximately 20-40% the level observed in WT mice (Chen et al 2012), suggesting that these hypomorphic mice could serve as a model of reduced, but not abolished, Akt1 expression, a condition more characteristic of the human disease state.…”
Section: Introductionmentioning
confidence: 99%